Problem manipulacji dziećmi i młodzieżą w procesie wychowania na podstawie uwag A.S. Kaufmana - Strzyżyński, Przemysław Strzyżyński (Poznańskie Studia Teologiczne, 2012)
The article presents the ethical conditions of an approved manipulation in the concept of A.S. Kaufman. The concept is a foundation for the question of the existence of educational manipulation. One of the points of the article is the observation that in the upbringing and education manipulation is done to the pupils. This paper presents a proposal of ethically justified manipulation of pupils. One of the conditions is, for example, that the person manipulating must treat pupils as the target, rather than the agent. Keywords